Science Fiction as an Instructional Strategy: Foundations, Procedures, and Results for Pre-service Teachers - ÖNEN ÖZTÜRK, FATMA; AĞLARCI ÖZDEMİR, OYA (Springer Science and Business Media B.V., 2022)
Science fiction (SF) combines realistic and imaginary elements of science and technology and develops students’ imagination, creativity, and interest in science. Therefore, the aim of this study is to examine SF stories written by pre-service science teachers (PSTs) in terms of various textual and science variables. The case study of SF story writing aimed to develop a theoretical framework to analyze how narrative elements, plot structure, agency, the nature of science content, characteristics of the SF genre, and ethics in scientific research are included in the stories of a group of Turkish PSTs. The participants of the study were 58 pre-service teachers enrolled in the science education department at a public university in Turkey. Working in groups, they wrote 13 different SF stories. The stories were analyzed with a rubric including two parts: narrative and other story elements and the characteristics of the SF genre. The results showed that the stories included fictional and realistic features of science and technology, scientific concepts, and details about scientific realities. The stories addressed the social and cultural embeddedness of scientific knowledge and details about the scientific method. However, the originality is limited in many stories as they had traces from popular movies, books, and TV series. The stories did consider a range of ethical issues, including unauthorized experimentation and manipulating scientific information for personal, political, and financial interests. The current study could contribute to the literature about the use and assessment of SF stories in science education. © 2021, Ministry of Science and Technology, Taiwan.
Keywords: Nature of science; Science education; Science fiction story; Teacher education